2015
DOI: 10.3126/on.v12i1.12252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seasonal variation on Growth Performance of Mirror carp (Cyprinus carpio Ver. specularis) in Earthen Nursery Ponds

Abstract: The experiment was conducted to determine the effect of seasonal variation on growth performance of Cyprinus carpio fry in six earthen ponds during December 2011 to June 2012 covering winter (WS) and summer season (SS , in SS respectively. Therefore, it can be concluded that mirror carp fry production was better in SS than in WS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In the present study, the growth rate was lower and FCR was comparatively poor which is due to severe winter season during the period of experiment (November–January). This is in agreement with Hossain, Khatun, Kamal, Habib, Tumpa, Subba and Hossain () who reported that growth rate and total production of mirror carp, Cyprinus carpio Ver. Specularis was very poor in winter season.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the growth rate was lower and FCR was comparatively poor which is due to severe winter season during the period of experiment (November–January). This is in agreement with Hossain, Khatun, Kamal, Habib, Tumpa, Subba and Hossain () who reported that growth rate and total production of mirror carp, Cyprinus carpio Ver. Specularis was very poor in winter season.…”
Section: Discussionsupporting
confidence: 92%
“…Taher et al (2014) recorded DGR of 3.16, SGR of 1.85 % day −1 and FCR of 2.63 for common carp fed 5 % feeding level in floating cages. Mirror carp (C. carpio) recorded SGR of 4.95 and 4.80 % day -1 in two densities during 90 days (Hossain et al, 2014). Taher et al (2018) pointed out that SGR of 2.44 % day −1 and FCR of 2.12 for common carp reared in semi-closed system for 52 days.…”
Section: Discussionmentioning
confidence: 99%